SAT0190 Reduction of serum immunoglobulin free light chains upon rituximab (anti-CD20) treatment correlates with decreased disease activity in patients with primary sjögren's syndrome. (23rd January 2014) - Bruining, D.M.; Pollard, R.P.E.; Moerman, R.; Meiners, P.M.; Meijer, J.M.; Burgerhof, H.J.; Vissink, A.; Kroese, F.G.M.; Bootsma, H.
Abstract : Background: Immunoglobulin free light chains (FLCs) are short-lived products of B lymphocytes and possess a wide range of immunological properties as signaling effectors or anti-inflammatory molecules. There is an upcoming interest in the role of circulating FLCs in the pathophysiology and monitoring of disease activity in a variety of autoimmune diseases like rheumatoid arthritis, systemic lupus erythematosus and Sjögren's syndrome. Objectives: To assess whether serum FLC changes upon rituximab (anti-CD20) therapy in primary Sjögren's syndrome (pSS) patients compared to a placebo group correlate with changes in disease activity. Methods: At baseline, serum of 30 pSS patients and 40 random, age and sex matched healthy blood donors was collected. Subsequently, in a randomized, double-blind, placebo-controlled design, 20 pSS patients were treated with rituximab (1000 mg) and 10 patients were treated with placebo infusions on days 1 and 15. FLC kappa and lambda concentrations were measured at baseline (pSS patients and controls) and at weeks 5, 12, 36 and 48 after rituximab or placebo treatment (pSS patients). At the same time points, rheumatoid factor and serum IgG were measured and the European Sjögren's syndrome disease activity index (ESSDAI) was completed. Results: At baseline, serum FLC concentrations were significantly increased in patients with pSS compared to healthy individuals (kappa: mean (±SD) 28.49 (±18.24) mg/l versus 7.20 (±2.67) mg/l; lambda: mean (±SD) 29.38 (±18.01) mg/l versus 12.50 (±4.46) mg/l). Over time, FLC kappa and lambda concentrations decreased in patients treated with rituximab, p<0.0003, p<0.005, p<0.005 and p<0.03, for baseline versus 5, 12, 36 and 48 weeks after treatment, respectively. Furthermore, high correlations between serum IgG and FLC kappa concentration (r=0.79, p<0.0001) and serum IgG and FLC lambda concentration (r=0.80, p<0.0001) were found as well as a high correlation between FLC kappa concentration and ESSDAI (r=0.46, p<0.0001) and FLC lambda concentration and ESSDAI (r=0.42, p<0.0001). In the placebo group, no treatment related decrease of serum FLCs could be detected, neither of rheumatoid factor, serum IgG and ESSDAI. Conclusions: A decrease in FLC concentrations reflects a decrease of disease activity in pSS patients. This decrease in FLC concentrations can be used as a biomarker to monitor changes in disease activity exerted by rituximab treatment. Disclosure of Interest: D. M. Bruining: None Declared, R. P. E. Pollard: None Declared, R. Moerman: None Declared, P. M. Meiners Grant/Research support from: Roche, Woerden, the Netherlands, J. M. Meijer Grant/Research support from: Roche, Woerden, the Netherlands, H. J. Burgerhof: None Declared, A. Vissink Grant/Research support from: Roche, Woerden, the Netherlands, F. G. M. Kroese: None Declared, H. Bootsma Grant/Research support from: Roche, Woerden, the Netherlands